Antibacterial Activity of Toothpaste Containing Sunflower Seed Extract against Staphylococcus aureus In Vitro - Putri Sianipar, Agnes Raiwana; Syahputra, Armia; Ervina, Irma; Amalia, Martina (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The increasing prevalence of oral bacterial infections and growing concerns regarding the long-term use of synthetic antibacterial agents have encouraged the exploration of natural alternatives in oral care products. This study aimed to evaluate the antibacterial effectiveness of toothpaste containing sunflower seed extract (Helianthus annuus Linn.) against Staphylococcus aureus ATCC® 29213 in vitro. Sunflower seeds were extracted using maceration, followed by phytochemical screening to identify bioactive secondary metabolites. The extract was formulated into toothpaste at concentrations of 2.5%, 5%, and 10%. A commercial antibacterial toothpaste (Siwak-F) was used as a positive control, while toothpaste base without antibacterial agents served as a negative control. Physicochemical characteristics of the formulations, including organoleptic properties, homogeneity, pH, spreadability, and viscosity, were evaluated to ensure formulation quality. Antibacterial activity was assessed using the agar well diffusion method on Mueller–Hinton Agar, and inhibition zone diameters were measured after 24 hours of incubation at 37°C. Statistical analysis was performed using the Kruskal–Wallis test followed by the Mann–Whitney post hoc test. The results demonstrated a concentration-dependent increase in antibacterial activity. Toothpaste containing 10% sunflower seed extract produced the largest inhibition zone and exhibited antibacterial activity comparable to the positive control, with no statistically significant difference. Lower concentrations (2.5% and 5%) also showed significant antibacterial effects compared to the negative control. These findings indicate that sunflower seed extract-based toothpaste has strong potential as a natural antibacterial dentifrice and may serve as a safer alternative to synthetic antibacterial agents in oral healthcare.